Improving the Students’ Skill in Writing English Abstract through the Directed Writing Activity (DWA) - Sigit Budisantoso (Jurnal Pendidikan Humaniora, 2014)
Abstract: Every year, most of the fifth-semester students in the Accounting Department, State Poly-technic of Malang always had a problem in writing English abstracts. This study was intended to im-prove students’ skill in writing English abstracts through the Directed Writing Activity (DWA). This research is a collaborative classroom action research. The data were collected through students’ portfolios, questionnaires on the students’ responses, and the observation sheet on the teacher’s performance. The assessment was done by evaluating the students’ portfolios, the students’ res-ponses on the DWA implementation in their classroom, and the observation on the teacher’s perfor-mance. After evaluating all the data, it can be concluded that the DWA was successfully done in class 3A, semester 5, the Accounting Department, State Polytechnic of Malang.Key Words: skill in writing, english abstract, directed writing activity Abstrak: Sebagian besar mahasiswa semester 5 Jurusan Akuntasi, Politeknik Negeri Malang bermasa-lah dengan penulisan abstrak Inggris setiap tahunnya. Penelitian ini bertujuan untuk meningkatkan kemampuan mahasiswa menulis abstrak Inggris melalui Directed Writing Activity (DWA). Penelitian ini merupakan collaborative classroom action research. Data dikumpulkan dari portofolio siswa, kuesioner tanggapan siswa, dan lembar observasi kinerja dosen. Penilaian dilakukan dengan mengeva-luasi portofolio siswa, tanggapan siswa tentang pelaksanaan DWA di kelas, dan pengamatan kinerja guru. Simpulannya adalah bahwa DWA berhasil dilakukan di kelas 3A, semester 5, Jurusan Akuntansi, Politeknik Negeri Malang.Kata kunci: kemampuan menulis, abstrak inggris, directed writing activity